2013
DOI: 10.2147/ndt.s36394
|View full text |Cite
|
Sign up to set email alerts
|

The use of psychotropic medication during pregnancy: how about the newborn?

Abstract: Infants are at risk of developing symptoms of Poor Neonatal Adaptation (PNA) after exposure to psychotropic drugs in utero. Such symptoms are largely similar after exposure to antidepressants, antipsychotics and benzodiazepines and consist of mostly mild neurologic, autonomic, respirator and gastro-intestinal abnormalities. Most symptoms develop within 48 hours after birth and last for 2–6 days. After exposure to Selective Serotonin Reuptake Inhibitors (SSRIs), mirtazapine or venlafaxine in utero, breastfeedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 95 publications
(224 reference statements)
1
66
0
Order By: Relevance
“…61,62 Approximately 1.8% of pregnant mothers use antidepressants and 3.0% use benzodiazepines. 63,64 Selective serotonin reuptake inhibitors (SSRIs), selective norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), and benzodiazepines are associated with NAS. 61,64 Women with mental health disorders are also at increased risk of substance abuse.…”
Section: Growing Epidemiologymentioning
confidence: 99%
“…61,62 Approximately 1.8% of pregnant mothers use antidepressants and 3.0% use benzodiazepines. 63,64 Selective serotonin reuptake inhibitors (SSRIs), selective norepinephrine reuptake inhibitors (SNRIs), tricyclic antidepressants (TCAs), and benzodiazepines are associated with NAS. 61,64 Women with mental health disorders are also at increased risk of substance abuse.…”
Section: Growing Epidemiologymentioning
confidence: 99%
“…The analysis was inconclusive as to which of the drugs is associated most strongly with the risk of PNAS in newborns, but it was established that the symptoms may affect from 20% to 77% of children exposed to SSRIs during foetal life [35]. Some of the studies also indicated an increased risk linked to the use of paroxetine and fluoxetine [36]. When using venlafaxine, the risk of PNAS is comparable to that associated with the use of SSRIs [37].…”
Section: Poor Neonatal Adaptation Syndrome (Pnas)mentioning
confidence: 99%
“…30,91 However, two SSRIs including fluoxetine and particularly paroxetine are not appropriate for first-line treatment because these drugs are the most frequently associated with congenital malformations and PNAS. 27,28,35,45,95 Nonetheless, these antidepressants may be chosen in women with OCD who do not respond or cannot tolerate other SSRIs due to low elevation of absolute risk of birth defects. 27,28,96,97 Sertraline and citalopram/escitalopram seem to be a more favorable option in the pregnancy period.…”
Section: Drug Optionsmentioning
confidence: 99%